Conformational and functional transitions and in silico analysis of a serine protease from conidiobolus brefeldianus (MTCC 5185) - Shukla, Ekta; Agrawal, Sanskruthi B.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2017)
This work describes functional and structural transitions of a novel protease isolated from Conidiobolus brefeldianus MTCC 5185 (Cprot), in detail using biophysical and bioinformatics tools. The commercial importance of Cprot in silk and leather industries made it an interesting candidate for structural investigations. Cprot possesses 8.2%alpha-helix, 31.1% beta-sheet and 23.8% turns. The enzyme was found to be active over a wide pH range and up to 55 degrees C. The protease was also stable in organic solvents up to 50% (v/v) concentration of alcohols and DMSO for >24 h and in 2 M guanidine hydrochloride for >12 h. Cprot was also resistant to trypsin, chymotrypsin, proteinase K and fluorinated alcohols (5-10%). The melting temperatures observed for the native Cprot and for the enzyme treated under various stress conditions correlated well with the corresponding structural and functional transitions obtained. The structural information was supported by the homology model of its closest homologue from C. coronatus; revealing its similarity to PA clan of proteases (Proteases of mixed nucleophile, superfamily A), with His-64, Asp-113 and Ser-208 as putative catalytic triad. Three tryptophan residues in Cprot are surrounded by positively charged residues, as evident from solute quenching studies and homology model. (C) 2017 Elsevier B.V. All rights reserved.

Pioglitazone inhibits advanced glycation induced protein modifications and down-regulates expression of RAGE and NF-kappa B in renal cells - Adeshara, Krishna A.; Agrawal, Sanskruthi B.; Gaikwad, Sushama M.; Tupe, Rashmi S. (International Journal of Biological Macromolecules, 2018)
The present work aims to determine the effect of pioglitazone on in-vitro albumin glycation and AGE-RAGE induced oxidative stress and inflammation. Bovine serum albumin was glycated by methylglyoxal in absence or presence of pioglitazone. Glycation markers (fructosamine, carbonyl groups, (l-amyloid aggregation, thiol groups, bilirubin binding capacity and AOPP); protein conformational changes (native-PAGE and HPLC analysis) were determined. Cellular study was done by estimating antioxidants, ROS levels, expression profile of membrane RAGE, NF-kappa B and levels of inflammatory cytokines (IL-6, TNF-alpha) using HEK-293 cell line. We observed that levels of glycation markers were reduced at higher concentration of pioglitazone as compared to glycated albumin. Structural analysis of glycated albumin showed inhibition of protein migration and structural changes when treated with pioglitazone. Pioglitazone has potentially restored cellular antioxidants and reduced levels of IL-6 and TNF-alpha by declining expression of membrane RAGE and NF-kappa B. In conclusion, pioglitazone preferentially binds to protein and alleviates protein structural changes by maintaining its integrity. Additionally, it suppresses RAGE and NF-kappa B levels hence alleviate cellular oxidative stress and inflammation. (C) 2018 Elsevier B.V. All rights reserved.

Investigation of structural and saccharide binding transitions of Bauhinia purpurea and Wisteria floribunda lectins - Agrawal, Sanskruthi B.; Ghosh, Deepanjan; Gaikwad, Sushama M. (Archives of Biochemistry and Biophysics, 2019)
Two novel medicinally important legume lectins from Bauhinia purpurea (BPL) and Wisteria floribunda (WFL) possessing extended sugar binding site were investigated for functional and conformational transitions using biochemical and biophysical techniques as well as bioinformatical tools. Homology model of BPL was constructed using the Schrodinger suite and docked with N-acetyl galactosamine and T-antigen disaccharide (Gal beta 1-3GalNAc alpha O-Me). The longer loop D in the structure of WFL compared to that in BPL was found to be responsible for its specificity to LacdiNac (beta-D-GalNAc-[1 -> 4]-DGlcNAc) over Gal beta 1-3GalNAc. BPL remained functionally stable up to 40 degrees C whereas WFL remained stable upto 70 degrees C indicating the strength of the sugar binding site geometry. Both the lectins showed intense but non-specific secondary structure in the range of 65-90 degrees C. WFL showed rapid aggregation above 80 degrees C as indicated by light scattering intensity. The lectins showed simultaneous dissociation and multistate unfolding in the vicinity of GdnHCl. At pH 1.0, both the lectins exhibited molten globule like structures, which were characterized further and were found to respond in a different way towards denaturants. The results have provided valuable insights into the molecular basis of the activity and stability of the two lectins.
Keywords: Conformation; Homology model; Lectin; Molten globule; saccharide binding; Thermal aggregation

Anticancer activity of lectins from bauhinia purpurea and wisteria floribunda on breast cancer MCF-7 cell lines - Agrawal, Sanskruthi B.; Gupta, Neha; Bhagyawant, Sameer S.; Gaikwad, Sushama M. (Protein and Peptide Letters, 2020)
Background: Individual and collaborative efforts are being made worldwide in search of effective chemical or natural drugs with less severe side-effects for treatment of cancer. Due to the specificity and selectivity properties of lectins for saccharides, several plant lectins are known to induce cytotoxicity into tumor cells. Objective: To study the antiproliferative activity of two N-acetyl galactosamine specific plant lectins from seeds of Bauhinia purpurea and Wisteria floribunda against MCF-7 Breast cancer cell lines. Methods: MTT, lactate dehydrogenase (LDH) leakage, reactive oxygen species (ROS), and caspase-3 assays and flow cytometry for cell cycle analysis were performed. Results: The agglutinins BPL and WFL; 446 mu gml(-1) (2.2 mu M) and 329 mu gml(-1) (2.8 mu M), respectively caused remarkable concentration-dependent antiproliferative effect on MCF-7. The effect was seen to be a consequence of binding of the lectin to the cell surface and triggering S and G2 phase arrest. Apoptosis induced was found to be associated with LDH leakage, cell cycle arrest and ROS generation. The apoptotic signal was observed to be amplified by activation of caspase-3 resulting in cell death. Conclusion: The study provides a base for detailed investigation and further use of lectins in cancer studies.
Keywords: anti-cancer; antiproliferative; Apoptosis; caspase-3; cell cycle arrest; Lectins; MCF-7; reactive oxygen species

Mechanistic insight into differential interactions of iron oxide nanoparticles with native, glycated albumin and their effect on erythrocytes parameters - Nisar, Akib; Ajabia, Devangi K.; Agrawal, Sanskruthi B.; Varma, Sanjana; Chaudhari, Bhushan P.; Tupe, Rashmi S. (International Journal of Biological Macromolecules, 2022)
Nanoparticles and protein bioconjugates have been studied for multiple biomedical applications. We sought to investigate the interaction and structural modifications of bovine serum albumin (BSA) with iron oxide nanoparticles (IONPs). The IONPs were green synthesized using E. crassipes aqueous leaf extract following characterization using transmission electron microscopy, energy dispersive X-ray analysis and X-ray diffraction. Two different concentrations of native/glycated albumin (0.5 and 1.5 mg/ml) with IONPs were allowed to interact for 1 h at 37 degrees C. Glycation markers, protein modification markers, cellular antioxidant, and hemolysis studies showed structural modifications and conformational changes in albumin due to the presence of IONPs. UV-visible absorbance resulted in hyperchromic and bathochromic effects of IONPs-BSA conjugates. Fluorescence measurements of tyrosine, tryptophan, advanced glycated end products, and ANS binding assay were promising and quenching effects proved IONPs-BSA conjugate formation. In FTIR of BSA-IONPs, transmittance was increased in amide A and B bands while decreased in amide I and II bands. In summary, native PAGE, HPLC, and FTIR analysis displayed a differential behaviour of IONPs with native and glycated BSA. These results provided an understanding of the interaction and structural modifications of glycated and native BSA which may provide fundamental repercussions in future studies.
Keywords: Albumin; Glycation; iron oxide nanoparticles